Comparison of boiling and orbital shaking extraction of vitamin B12 from Ulva lactuca using 2-Level Factorial Design - Ruslan, Fatin Shazwani; Darnis, Deny Susanti; Mohammad Nor, Normawaty; Bakhtiar, M. Taher; Aminudin, Nurul Iman (Malaysian Natural Products Society (MNPS), 2021)
Vitamin B12 deficiency which is common in strict vegetarians, the elderly, and who are vulnerable to an autoimmune disorder that prevents its efficient uptake. Many algae are rich with B12, such as edible green macroalgae Ulva lactuta, that been reported higher in cobalamin, and the best bioavailability of the algae vitamin B12 is based on its type, active or inactive corrinoid content. This study focuses on the different extraction methods of vitamin B12 from different types of dried U. lactuca, particularly freeze-dried, oven-dried, sun-dried, and air-dried sample. Also, the effect of solvent:solvent (MeOH:H2O), solute:solvent ratio, and pH on the total vitamin B12 content were also been screened using 2-Level Factorial design from RSM. The retention time (RT) from HPLC of all crude extracts were corresponded with the RT of standard cyanocobalamin (CN-Cbl) at 1.9 minutes. Oven-dried and sun-dried U. lactuca gave the highest CN-Cbl yield, 0.0210 mg/mL (parameters; 25:75 % MeOH:H2O, pH 3, 3 g: 60 mL solute:solvent ratio and 0.0356 mg/mL (parameters; 25:75 % MeOH:H2O, pH 3, 3 g: 90 mL solute:solvent ratio) when extracted using boiling and orbital shaking extraction method, respectively. However, the extraction of CN-Cbl by orbital shaking gave insignificant (p > 0.05) result on the yield of CN-Cbl, compared to boiling method when oven-dried sample were extracted (p < 0.05). Hence, the concentration of CN-Cbl increased significantly (p < 0.05) with decreasing MeOH:H2O, solute:solvent ratios and pH when U. lactuca was subjected to oven-dried drying method, and extracted using boiling extraction method.